"역함수를 이용한 치환적분"의 두 판 사이의 차이
둘러보기로 가기
검색하러 가기
Pythagoras0 (토론 | 기여) |
Pythagoras0 (토론 | 기여) |
||
2번째 줄: | 2번째 줄: | ||
* 역함수를 이용한 치환적분법 | * 역함수를 이용한 치환적분법 | ||
− | + | :<math>\int f(x)\,dx=xf(x)-\int xf'(x)\,dx+xf(x)-\int f^{-1}(f(x))f'(x)\,dx+xf(x)-G(f(x))</math> | |
− | |||
− | |||
− | <math>\int f(x)\,dx=xf(x)-\int xf'(x)\,dx+xf(x)-\int f^{-1}(f(x))f'(x)\,dx+xf(x)-G(f(x))</math> | ||
− | |||
여기서 <math>G(x)= \int f^{-1}(x)\,dx</math> | 여기서 <math>G(x)= \int f^{-1}(x)\,dx</math> | ||
− | + | ==예== | |
− | + | * 다음 부정적분 | |
− | <math>\int \sqrt{\frac{x}{1-x}}\,dx</math> | + | :<math>\int \sqrt{\frac{x}{1-x}}\,dx</math> |
− | + | * $G$는 다음과 같다 | |
<math>G(x)=\int f^{-1}(x)\,dx= \int\frac{x^2}{1+x^2}\,dx=\int(1-\frac{1}{1+x^2})\,dx=x-\arctan x+C</math> | <math>G(x)=\int f^{-1}(x)\,dx= \int\frac{x^2}{1+x^2}\,dx=\int(1-\frac{1}{1+x^2})\,dx=x-\arctan x+C</math> | ||
− | |||
따라서, | 따라서, | ||
− | + | :<math>\int \sqrt{\frac{x}{1-x}}\,dx= (x-1)\sqrt{\frac{x}{1-x}}+\arctan{\sqrt{\frac{x}{1-x}}}+C</math> | |
− | <math>\int \sqrt{\frac{x}{1-x}}\,dx= (x-1)\sqrt{\frac{x}{1-x}}+\arctan{\sqrt{\frac{x}{1-x}}}+C</math> | ||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
56번째 줄: | 19번째 줄: | ||
==관련된 항목들== | ==관련된 항목들== | ||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
[[분류:적분]] | [[분류:적분]] |
2013년 2월 11일 (월) 08:16 판
개요
- 역함수를 이용한 치환적분법
\[\int f(x)\,dx=xf(x)-\int xf'(x)\,dx+xf(x)-\int f^{-1}(f(x))f'(x)\,dx+xf(x)-G(f(x))\] 여기서 \(G(x)= \int f^{-1}(x)\,dx\)
예
- 다음 부정적분
\[\int \sqrt{\frac{x}{1-x}}\,dx\]
- $G$는 다음과 같다
\(G(x)=\int f^{-1}(x)\,dx= \int\frac{x^2}{1+x^2}\,dx=\int(1-\frac{1}{1+x^2})\,dx=x-\arctan x+C\) 따라서, \[\int \sqrt{\frac{x}{1-x}}\,dx= (x-1)\sqrt{\frac{x}{1-x}}+\arctan{\sqrt{\frac{x}{1-x}}}+C\]